Optimalisasi Pemasangan Trafo Sisip untuk Perbaikan Drop Tegangan Pelanggan pada Trafo RTP 033 ULP Peureulak PT PLN (Persero) - hasanah, mardini; Puspitasari, Pipit; Oktavia, Yosa; Qatrunnada, Rusvaira; Septiyeni, Tesya Uldira (Power Elektronik : Jurnal Orang Elektro, 2025)
This study aims to analyze the installation of insert transformers in overcoming voltage drop problems in customers at the RTP 033 transformer of ULP Peureulak PT PLN (Persero). The research was conducted at transformer RTP 033 located in the Paya Uno area, Rantau Peureulak District, East Aceh, which experienced significant voltage drop problems. Through manual calculations using the formula in the RST phase, the voltage drop values were 22.99%, 20.63%, and 21.05% before the installation of the insert transformer. After the installation of the insert transformer, the voltage drop value was successfully reduced below the permitted standard of less than 5% with the voltage drop value for each phase being 2.18%, 2.63%, and 3.06%. The measurement results in the field show a significant increase in distribution voltage at points that previously experienced a decrease. In addition to improving voltage quality, the installation of the insert transformer also had a positive impact on increasing electrical energy consumption. There was an increase in kWh sales of 13.14% after the installation of the insert transformer. Based on the research results, it can be concluded that the installation of an insert transformer is an effective solution to overcome the voltage drop problem in the distribution network. Thus, the quality of electricity service to customers can be improved, and the risk of damage to electronic equipment due to voltage fluctuations can be minimized.